Emerging Functions of Nanostructured Porous Silicon—With a Focus on the Emissive Properties of Photons, Electrons, and Ultrasound - Koshida, Nobuyoshi; Nakamura, Toshihiro (Frontiers in Chemistry, 2019)
Recent topics of application studies on porous silicon (PS) are reviewed here with a focus on the emissive properties of visible light, quasiballistic hot electrons, and acoustic wave. By exposing PS in solvents to pulse laser, size-controlled nc-Si dot colloids can be formed through fragmentation of the PS layer with a considerably higher yield than the conventional techniques such as laser ablation of bulk silicon and sol-gel precursor process. Fabricated colloidal samples show strong visible photoluminescence (~40% in quantum efficiency in the red band). This provides an energy- and cost-effective route for production of nc-Si quantum dots. A multiple-tunneling transport mode through nc-Si dot chain induces efficient quasiballistic hot electron emission from an nc-Si diode. Both the efficiency and the output electron energy dispersion are remarkably improved by using monolayer graphene as a surface electrode. Being a relatively low operating voltage device compatible with silicon planar fabrication process, the emitter is applicable to mask-less parallel lithography under an active matrix drive. It has been demonstrated that the integrated 100 × 100 emitter array is useful for multibeam lithography and that the selected emission pattern is delineated with little distortion. Highly reducing activity of emitted electrons is applicable to liquid-phase thin film deposition of metals (Cu) and semiconductors (Si, Ge, and SiGe). Due to an extremely low thermal conductivity and volumetric heat capacity of nc-Si layer, on the other hand, thermo-acoustic conversion is enhanced to a practical level. A temperature fluctuation produced at the surface of nc-Si layer is quickly transferred into air, and then an acoustic wave is emitted without any mechanical vibrations. The non-resonant and broad-band emissivity with low harmonic distortions makes it possible to use the emitter for generating audible sound under a full digital drive and reproducing complicated ultrasonic communication calls between mice.